2022
DOI: 10.1111/tpj.16048
|View full text |Cite
|
Sign up to set email alerts
|

ANTHRACNOSE RESISTANCE GENE2 confers fungal resistance in sorghum

Abstract: Sorghum is an important food and feed crop globally; its production is hampered by anthracnose disease caused by the fungal pathogen Colletotrichum sublineola (Cs). Here, we report identification and characterization of ANTHRACNOSE RESISTANCE GENE 2 (ARG2) encoding a nucleotide-binding leucine-rich repeat (NLR) protein that confers race-specific resistance to Cs strains. ARG2 is one of a cluster of several NLR genes initially identified in the sorghum differential line SC328C that is resistant to some Cs strai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…The new locus is designated ANTHRACNOSE RESISTANCE GENE 4 ( ARG4 ), following our sequential naming of three other anthracnose resistance loci ( ARG1 to ARG3 ) identified recently using different mapping populations. ARG1 and ARG2 have been published (Lee et al., 2022; Mewa et al., 2023) while ARG3 is pending publication. The segregation pattern of the SAP135 x TAM428 mapping populations varied when plants were inoculated with different strains suggesting SAP135 carries multiple independent loci conferring resistance to different strains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The new locus is designated ANTHRACNOSE RESISTANCE GENE 4 ( ARG4 ), following our sequential naming of three other anthracnose resistance loci ( ARG1 to ARG3 ) identified recently using different mapping populations. ARG1 and ARG2 have been published (Lee et al., 2022; Mewa et al., 2023) while ARG3 is pending publication. The segregation pattern of the SAP135 x TAM428 mapping populations varied when plants were inoculated with different strains suggesting SAP135 carries multiple independent loci conferring resistance to different strains.…”
Section: Resultsmentioning
confidence: 99%
“…ARG1 confers broad‐spectrum fungal resistance in sorghum. The second gene ANTHRACNOSE RESISTANCE GENE 2 ( ARG2 ) encoding another NLR protein that confers race‐specific resistance to C. sublineola strains was also identified and characterized in our lab (Mewa et al., 2023). These data, collectively, provided new insights into the genetic control of plant immunity in sorghum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the testing sites, Haramaya stands out as the environment where the majority of accessions demonstrated a resistant reaction to anthracnose (Table S1 ). Recent studies isolated ANTHRACNOSE RESISTANCE GENES (ARG1, ARG2, ARG4, and ARG5) encoding nucleotide-binding leucine-rich repeats (NLR) proteins [ 20 – 22 ]. It is worth noting that the current study identified new loci containing new NLRs and RLKs but none of the ARGs genes were identified showing differences in mapping through biparental and GWAS approaches and differences in field and greenhouse-based genetic screens for disease resistance.…”
Section: Discussionmentioning
confidence: 99%